Comorbidity of Bipolar Disorder and Multiple Sclerosis: A Case Report - Necla Keskin; Soner Cakmak; Lut Tamam; Ahmet Turan Evlice (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Multiple sclerosis is a chronic demyelinating disease of a central nervous system. Neuropsychiatric symptoms are common in multiple sclerosis and bipolar disorder is one of the most common psychiatric disorders that coexist with multiple sclerosis. Manic episodes may be the first presenting symptom of multiple sclerosis as comorbid pathology or as an adverse effect of pharmacotherapies used in multiple sclerosis. The comorbidity of bipolar disorder and multiple sclerosis is well-proven but its etiology is not known and investigated accurately. Recent studies support a common genetic susceptibility. Management of bipolar disorder in multiple sclerosis is based on evidence provided by case reports and treatment should be individualized. In this report, the association between bipolar disorder and multiple sclerosis, epidemiology, ethiology and treatment is discussed through a case had diagnosed as multiple sclerosis and had a manic episode with psychotic features. [Cukurova Med J 2013; 38(4.000): 832-836]